The relation between fluid intelligence and the general factor as a function of cultural background: A test of Cattell's investment theory - Ann Valentin Kvist; Jan-Eric Gustafsson (Institute for Labour Market Policy Evaluation (IFAU), 2007)
According to Cattell's (1987) Investment theory individual differences in acquisition of knowledge and skills are partly the result of investment of Fluid Intelligence (Gf) in learning situations demanding insights in complex relations. If this theory holds true Gf will be a factor of General Intelligence (g) because it is involved in all domains of learning. The purpose of the current study was to test the Investment theory, through investigating effects on the relation between Gf and g of differential learning opportunities for different subsets of a population. A second-order model was fitted with confirmatory factor analysis to a battery of 17 tests hypothesized to measure four broad cognitive abilities The model was estimated for three groups with different learning opportunities (N = 2358 Swedes, N = 620 European immigrants, N = 591 non-European immigrants), as well as for the total group. For this group the g Gf relationship was 0.83, while it was close to unity within each of the three subgroups. These results support the Investment theory.
Keywords: J24; J61; 330; Structure of intelligence; Cattell's Investment theory; fluid Intelligence; general Intelligence; Kognition; Lernprozess; Lernpsychologie; Kulturelle Identität; Test; Theorie; Schweden